Monitoring and Improving Sleep Quality in Professional Athletes - Guzik, Marcelina; Wyleciał, Zuzanna; Dąbrowski, Patryk; Ząber, Julia (Quality in Sport, 2025)
Introduction and Purpose: Sleep is a fundamental component of performance, recovery, and overall health in professional athletes. However, sleep disturbances—including insufficient duration, poor quality, and insomnia—are highly prevalent in this population due to factors such as early-morning training, late-evening competitions, transmeridian travel, and psychological stress. This review aims to provide a comprehensive summary of current knowledge regarding sleep monitoring techniques and evidence-based interventions to improve sleep in elite athletes. Methods: We conducted a structured literature search in PubMed, Embase, and UpToDate through May 2025. Eligible studies included systematic reviews, randomized controlled trials, observational studies, and consensus guidelines focusing on sleep in professional, elite, or Olympic-level athletes. Search terms included combinations of "sleep," "athletes," "interventions," and "performance." Findings were narratively synthesized under thematic headings. Current State of Knowledge: Up to 60% of elite athletes report poor sleep quality, and 27–37% exhibit insomnia symptoms during competition periods. Key contributors include circadian disruption, high training loads, pre-competition anxiety, and environmental/lifestyle factors. Assessment tools such as actigraphy and the Athlete Sleep Screening Questionnaire (ASSQ) are validated and widely used. Non-pharmacological strategies, especially sleep hygiene education, sleep extension, strategic napping, CBT-I, and light exposure demonstrate positive effects on sleep duration, quality, and performance. Melatonin shows potential for managing jet lag, though evidence in athletic settings remains limited. Sedatives are rarely studied and should be used with caution. Conclusions: Sleep problems are common and impactful in elite sport. Personalized, non-pharmacological approaches should be prioritized, while further research is needed to refine and validate targeted interventions.